Bupropion Mediated Effects on Depression, Attention Deficit Hyperactivity Disorder, and Smoking Cessation - Austin Clark; Brendan Tate; Bretton Urban; Ryan Schroeder; Sonja Gennuso; Shahab Ahmadzadeh; David McGregor; Brook Girma; Sahar Shekoohi; Alan D. Kaye (Health Psychology Research)
Bupropion had been in use since the late 1980s as an unconventional treatment for depression. Unlike other antidepressants, bupropion has no serotonergic activity and inhibits the reuptake of norepinephrine and dopamine. The drug has been used to treat depression, Attention Deficit Hyperactivity Disorder (ADHD), and smoking cessation. This investigation reviews the pharmacokinetic and pharmacodynamic effects of bupropion and its mechanisms of action and interactions with other drugs. We evaluated the efficacy of major on and off-label uses of bupropion, focusing on the indications, benefits, and adverse effects. Our review demonstrates that bupropion is superior to placebo and non-inferior to SSRIs such as escitalopram in treating major depressive disorder. More research is needed to determine positive patient-centered outcomes such as increases in quality of life. In the case of ADHD, the evidence for efficacy is mixed with poorly conducted randomized clinical trials, small sample sizes, and a lack of long-term assessments. The same is true in the case of bipolar disorder in which there is still limited and controversial data available on bupropion's safety and efficacy. In the case of smoking cessation, bupropion is found to be an effective anti-smoking drug with synergistic benefits when used as a combination therapy. We conclude that bupropion has the potential to provide benefit for a subset of patients who do not tolerate other typical antidepressants or anti-smoking therapies or for those whose treatment goals align with bupropion's unique side effect profile, such as smokers who wish to quit and lose weight. Additional research is needed to determine the drug's full clinical potential, particularly in the areas of adolescent depression and combination therapy with varenicline or dextromethorphan. Clinicians should use this review to understand the varied uses of the drug and identify the situations and patient populations in which bupropion can lend its greatest benefit.